Interactions among hypogeous fungi and wild boars in the subcontinental pine forest - Ławrynowicz, Maria; Faliński, Janusz B.; Bober, Joanna (Biodiversity: Research and Conservation, 2006)
Elaphomyces asperulus Vitt. is the most common hypogeous fungus in the subcontinental Scots pine forest Peucedano-Pinetum in Poland. Both conifers comprising the tree stand - Pinus sylvestris and Picea abies - form ectomycorrhizal associations between their roots and mycelium of Elaphomyces asperulus. In good habitat conditions, the fungus produces great number of fruit-bodies. They occur 1-10 cm beneath the soil surface under the moss and humus cover and are easily found by wild boars intensively rooting for food. The paper presents preliminary results of mycological analysis of 61 subplots situated in the Peucedano-Pinetum association, 1m2 each, rooted and unrooted. They indicate the stimulating role of wild boars in the fructification process and spread of spores of Elaphomyces.